Gender differences in health-related quality of life associated with abdominal obesity in a Korean population. Issue 1 (24th January 2014) - Choo, Jina; Jeon, Seonhui; Lee, Juneyoung
Abstract : Objectives: Overall obesity, as measured by body mass index (BMI), has been associated with a low level of health-related quality of life (HRQOL), but little is known about abdominal obesity. This cross-sectional study aimed to determine whether abdominal obesity, as measured by waist circumference (WC), would be significantly associated with HRQOL independent of overall obesity, and if so, whether the association would differ by gender among the Korean population. Design: Cross-sectional study. Setting: South Korea. Participants: Using data from the 2007–2009 Korea National Health and Nutrition Examination Survey, a total of 13 754 men and women aged 19–65 years were selected, and information about height (cm), weight (kg), WC (cm) and the EuroQOL-5 Dimensions (EQ-5D) scores for HRQOL were taken. Results: Not only an overall obesity (as categorised into obese, overweight or non-overweight groups based on BMI) but also an abdominal obesity (defined by WC ≥90 cm for men and ≥85 cm for women) was significantly associated with lower EQ-5D scores, after adjusting for age, gender, socioeconomic variables and a number of comorbidities. Even after adjusting BMI effect, the association between abdominal obesity and lower EQ-5D scores remained significant for women, but not for men. Conclusions: Among the Korean population aged 19–65 years, abdominal obesity was associated with impaired HRQOL, independently of overall obesity. Furthermore, this association differed by gender, being significant only for women. Therefore, primary healthcare professionals should pay attention to gender differences in the impact of obesity on HRQOL when evaluating population-based health programmes.